2021
DOI: 10.3389/fnagi.2020.616614
|View full text |Cite
|
Sign up to set email alerts
|

AD7c-NTP Impairs Adult Striatal Neurogenesis by Affecting the Biological Function of MeCP2 in APP/PSl Transgenic Mouse Model of Alzheimer's Disease

Abstract: The processes by which neural stem cells (NSCs) and neural precursor cells (NPCs) transform into the characteristic lineages observed in Alzheimer's disease (AD) are poorly characterized. Understanding these processes is of critical importance due to the increased prevalence of AD and the lack of effective AD strategies. Here, we used immunohistochemistry and Western blot to find out if MeCP2 was phosphorylated at a specific amino acid residue, Serine 421 (S421), and activated in response to AD-induced damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The AD7c-NTP is associated with neurodegeneration in AD, and suppression is partially mediated by the phosphorylation of MeCP2 at serine 421 (S421), in combination with DNA demethylation at GFAP, Nestin, and DCX promoter regions, which prevents MeCP2 from binding to its target cells and thus reducing transcription repression, and in turn induces gene expression. These genes may be involved in regeneration and determination of the fate of NSPCs (neural stem/progenitor cells) during striatum neurogenesis in adults [78].…”
Section: Creation Of Anscs In Intact and Damaged Brainsmentioning
confidence: 99%
“…The AD7c-NTP is associated with neurodegeneration in AD, and suppression is partially mediated by the phosphorylation of MeCP2 at serine 421 (S421), in combination with DNA demethylation at GFAP, Nestin, and DCX promoter regions, which prevents MeCP2 from binding to its target cells and thus reducing transcription repression, and in turn induces gene expression. These genes may be involved in regeneration and determination of the fate of NSPCs (neural stem/progenitor cells) during striatum neurogenesis in adults [78].…”
Section: Creation Of Anscs In Intact and Damaged Brainsmentioning
confidence: 99%
“…This gene encodes for a protein capable of binding methylated DNA and acting as a transcriptional repressor [55]. Although it is primarily linked to autism spectrum disorders, studies on animal models have indicated a potential association between MECP2 alterations and AD pathogenesis, as well as cognitive decline [56][57][58][59]. Moreover, recent research on humans suggests that MECP2 may unveil a novel etiopathogenetic mechanism of sporadic AD [60].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The authors suggested that this finding was due to de novo phosphorylation of MeCP2 after AD pathological injury, possibly acting to relieve transcriptional repression. 63 …”
Section: Dna Methylationmentioning
confidence: 99%
“…The authors suggested that this finding was due to de novo phosphorylation of MeCP2 after AD pathological injury, possibly acting to relieve transcriptional repression. 63 The implications of changes in expression of "reader" proteins in the context of neurodegenerative diseases require further investigation.…”
Section: Writers Erasers and Readersmentioning
confidence: 99%